Faktor Penghambat Penegakan Hukum Terhadap Kekerasan Perempuan Dalam Pacaran - Siti Nurlaila A. Imani; Suwitno Y. Imran; Apripari Apripari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to discuss factors inhibiting law enforcement against dating violence. This research uses empirical legal methods, namely based on phenomena and realities in society, then analyzed descriptively qualitatively and conclusions are given. The results of the research show that the factors inhibiting law enforcement of violence against women in relationships in the jurisdiction of the Gorontalo City Police Department are legal and enforcement factors where there are no articles or statutory regulations that specifically regulate violence in dating relationships; Police Resource Factors; Factors within the victim and family; and Lack of community participation and culture. Therefore, it is important to make extra efforts in the law enforcement process by the authorities against violence in dating relationships, and prioritize justice and safety for victims. This can be done by strengthening the legal substance, especially the sanctions imposed on perpetrators, including the commitment and consistency of the authorities in completing the process in question. Furthermore, the community, including parents and families, are expected to be more active and caring in providing protection movements for victims of violence in dating relationships. Apart from that, the importance of socializing the impact and legal sanctions that will be given to perpetrators who commit dating violence, especially for teenagers who are vulnerable to becoming perpetrators or victims.